An Amorphous MnO2/Lithiated NiO Nanosheet Array as an Efficient Bifunctional Electrocatalyst for Iron Molten Air Batteries. Issue 5 (8th April 2019) - Liu, Shuzhi; Gao, Shengyao; Cui, Baochen; Xiang, Wei; Liu, Xianjun; Han, Wei; Zhang, Jianhua
Abstract : Iron molten air battery is considered one of the promising batteries in next‐generation energy storage due to high theoretical specific energy density, cost efficiency, and environment‐friendly merits. Herein, an amorphous MnO2 /lithiated NiO nanosheet array is grown directly on a highly conductive nickel foam substrate to use as a bifunctional electrocatalyst in iron molten air batteries. The advantages of the nanosheet array structure are having more highly exposed active sites for electrochemical reactions, as well as a conductive stable 3D framework for allowing barrier‐free diffusion and transport of ions and oxygen gas. As a result, the amorphous MnO2 /lithiated NiO nanosheet array exhibits a promising catalytic activity for oxygen evolution reaction and oxygen reduction reaction with a voltage gap of only 0.29 V. The as‐assembled iron molten air battery shows an impressive rechargeability with the highest coulombic efficiency of nearly 100% through 200 cycles with an average discharge potential of ≈1.14 V at 500 °C. Moreover, the cell has a high rate response up to 6.7 C with a discharge voltage of above 0.9 V. The study achieves critical advances for iron molten air batteries without the use of precious metals in contrast with previous results using the Pd‐based catalyst. Abstract : An amorphous MnO2 /lithiated NiO nanosheet array is prepared, and exhibits an efficient bifunctional activity at promoting the kinetics of oxygen evolution reaction/oxygen reduction reaction. The as‐assembled iron molten air battery cycled stably over 200 cycles with the highest coulombic efficiency of up to 99.6% and an average discharge potential of ≈1.14 V at 500 °C in the air.